PENGARUH JOB CRAFTING DAN KINERJA KARYAWAN TERHADAP KINERJA ORGANISASI PT. BANK SYARIAH INDONESIA - Setia Budi, M. Arief; Zahira, Tsuraiya; Kamalia, Kamalia; Farizal, Ryan; Ansari, Ansari (Fakultas Ekonomi, 2025)
This study was conducted to determine and test the analysis of the influence of job crafting and employee performance on the performance of PT. Bank Syariah Indonesia Lhokseumawe Branch Office, totaling 85 people. The sample was taken using saturated samples or total sampling techniques, and is also called the census method. Given the relatively small population, all populations were used as respondents. The data analysis technique used was multiple linear regression through SPSS version 26. The test results revealed that partially job crafting had a positive and significant effect on the performance of PT. Bank Syariah Indonesia Lhokseumawe Branch Office. Partially employee performance had a positive and significant effect on the performance of PT. Bank Syariah Indonesia Lhokseumawe Branch Office. Simultaneously, job crafting and employee performance had a positive and significant effect on the performance of PT. Bank Syariah Indonesia Lhokseumawe Branch Office.